TP53 Mutations in Esophageal Squamous Cell Carcinoma - Leqi Zhong; Hongmu Li; Wuguang Chang; Yong Ao; Zhesheng Wen; Youfang Chen (Frontiers in Bioscience-Landmark, 2023)
The occurrence and development of esophageal cancer involve multiple genetic abnormalities that contribute to the malignant transformation of esophageal epithelial cells, followed by invasion and metastasis, leading to a poor outcome. Esophageal squamous cell carcinoma (ESCC) is the predominant histological subtype of esophageal malignancy in East Asia, with approximately half of newly diagnosed ESCC cases occurring in China. The TP53 tumor suppressor gene mutation is one of the most common mutations in ESCC. TP53 mutations are observed even in the early phases of esophageal carcinogenesis. Normal functions of the p53 network are lost in cells of ESCC patients who harbor the mutant TP53 gene, inducing tumor development, radiation resistance, chemotherapy resistance, and immune suppression, promoting progression and metastasis, thereby resulting in an overall poor prognosis. Although clinical trials of several pharmacological compounds targeting mutational TP53 have been explored, novel approaches are still urgently required to improve the observed dismal survival. A better understanding of the role of the mutant TP53 gene in human ESCC might lead to the discovery of innovative targeted therapies to treat this malignancy.